The use of the pediatric physeal slide-traction plate in the treatment of neer–horwitz grade IV proximal humeral fractures in children: A case report and literature review - Qi, Le; Jiang, Yikun; Wang, Yanbing; Peng, Chuangang; Wu, Dankai (Frontiers in Surgery, 2022)
Background Proximal humeral fractures (PHFs) are rare in children. Currently, the recommended surgical methods for severely displaced PHFs are closed reduction and percutaneous fixation using K-wires or intramedullary nailing, which are too loose to provide firm internal fixation. Adjuvant external fixation is usually required for older and high-weight children. This study aimed to introduce a novel surgical approach, pediatric physeal slide-traction plate fixation (PPSP), for Neer–Horwitz grade IV PHFs in children. Case summary A 9-year-old boy presented with left shoulder pain and swelling due to a car accident. Physical examination revealed a positive shoulder deformity and local tenderness. Additionally, we palpated the bony rubbing and abnormal movement without vascular or nerve injury. According to the radiographic result and Neer–Horwitz classification, the patient was diagnosed with Neer–Horwitz grade IV PHF. Considering the patient’s condition, we performed PPSP surgery. After 22 months of follow-up, the patient had satisfactory left shoulder function without any restriction of activities, and the follow-up showed good outcomes. Conclusion According to previous studies, PPSP is only used for femur fractures. To the best of our knowledge, this is the first in the treatment for PHFs. Given the satisfactory outcomes, it is a safe and effective method and may provide a reference to cure analogous patients in the future.